AF03 adjuvant improves anti-hemagglutinin and anti-neuraminidase immune responses induced by licensed seasonal quadrivalent influenza vaccines in mice. Issue 12 (17th March 2023) - Ustyugova, Irina V.; Pougatcheva, Svetlana; Farrell, Timothy; Strugnell, Tod; Ganesh, Vardhini; Zeldovich, Konstantin B.; Chivukula, Sudha; Goncalvez, Ana P.; Barro, Mario
Highlights: AF03 adjuvant induced 4–40-fold increases in homologous HAI titers against IIV4-SD and RIV4 vaccines. 10-fold increases in NAI titers observed against a homologous strain with AF03 addition. HA-specific binding titers against 30 heterologous recombinant HAs confirmed 4–70-fold increases. A novel method to assess a breadth of HA-specific immune response will be used in clinical trials. Abstract: Seasonal influenza remains a serious public health concern as the viral infection spreads easily from person to person and due to antigenic drift of neutralizing epitopes. Vaccination is the best method for disease prevention, however current seasonal influenza vaccines stimulate antibodies which are often effective against only antigenically similar strains. To boost the immune responses and increase vaccine effectiveness, adjuvants have been used for the past 20 years. The current study explores the use of oil-in-water adjuvant, AF03 to improve an immunogenicity of 2 licensed vaccines. A standard-dose inactivated quadrivalent influenza vaccine (IIV4-SD), containing both hemagglutinin (HA) and neuraminidase (NA) antigens, and recombinant quadrivalent influenza vaccine (RIV4), containing only HA-antigen were adjuvanted with AF03 in naïve BALB/c mouse model. Functional HA-specific antibody titers against all four homologous vaccine strains were enhanced by AF03, indicating potential increase in protective immunity. An increase in HA-specific total immunoglobulin G (IgG) binding titers were detected against homologous HAs, heterologous panel of 30 H3 HAs and seven Influenza B HAs. The neuraminidase inhibition (NAI) activity was significantly higher in IIV4-SD-AF03 group. Use of AF03 adjuvant improved the immune response to two influenza vaccines in a mouse model via an increase in functional and total antibodies against NA and a broad panel of HA-antigens.